2018
DOI: 10.1590/1981-6723.12717
|View full text |Cite
|
Sign up to set email alerts
|

Determination of inosine 5’-monophosphate (IMP) and guanosine 5’-monophosphate (GMP) in yeast extracts using UV spectroscopy and chemometrics

Abstract: This study proposed a method to determine the sum of the concentrations of inosine 5’-monophosphate (IMP) and guanosine 5’-monophosphate (GMP) in final and intermediate products through a combination of UV spectroscopy and multivariate calibration. Partial Least Squares regression (PLS regression) was used for the data analysis and the proposed methods presented errors of around 4 mg/L. In addition, the analysis cost is 10 times lower than the reference chromatographic method and the analytical frequency is 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We followed the protocol of Pereira to determine the amount of these nucleotides by spectrophotometric methods. The previous records of the nucleotidesabsorbance varies within the range of 200-300nm, with a peak at 250nm (Pereira et al, 2018). The measured absorbance of the nucleotides in our yeast extract has been found to be 3.00 at 250 nm.…”
Section: Determination Of Nucleotidesmentioning
confidence: 49%
See 3 more Smart Citations
“…We followed the protocol of Pereira to determine the amount of these nucleotides by spectrophotometric methods. The previous records of the nucleotidesabsorbance varies within the range of 200-300nm, with a peak at 250nm (Pereira et al, 2018). The measured absorbance of the nucleotides in our yeast extract has been found to be 3.00 at 250 nm.…”
Section: Determination Of Nucleotidesmentioning
confidence: 49%
“…The determination of the concentration of the nucleotides 5'IMP (inosine 5'-monophosphate) and 5'GMP (guanosine 5'-monophosphate) has been carried out by spectrophotometric method. Pereira and his colleagues found that the best absorbance of IMP and GMP can be obtained at wavelength of 250 nm (Pereira et al, 2018). Therefore, the absorbance of IMP and GMP was measured at 250nm using Thermo Electron Corporation, model number Genesys 10-S in liquid yeast extract sample.…”
Section: Determination Of Nucleotides Concentrationmentioning
confidence: 99%
See 2 more Smart Citations